PERAN PESANTREN MIFTAHUL QULUB DALAM MENANGKAL RADIKALISME MELALUI PENDEKATAN TASAWUF BERDASARKAN AL-QUR'AN SURAH AL-ANBIYA AYAT 107 - Maisaroh, Sofatul; Izza, Nuri Nailul (Jurnal Ushuluddin, 2025)
The phenomenon of radical ideologies propagated in the name of religion presents a critical challenge to both the religious harmony and social cohesion of Indonesian society. As traditional Islamic educational institutions, pondok pesantren hold a strategic position in nurturing students (santri) with a moderate outlook and refined moral character. This study aims to examine the role of Pondok Pesantren Miftahul Qulub in preventing religious radicalism through a Sufi-oriented educational framework, grounded in the values embodied in Surah Al-Anbiya' (21:107), which portrays Islam as a mercy to all of creation (rahmatan lil-‘alamin).Employing a qualitative case study approach, the research utilized participant observation and in-depth interviews involving the kiai (spiritual guide), ustadz (teachers), and santri as primary sources. Data analysis was carried out through stages of data reduction, presentation, verification, and drawing conclusions. The findings suggest that the pesantren performs a transformative function by integrating Sufi ethics into the spiritual formation of its students. This is achieved through sustained tazkiyat al-nafs (purification of the soul) and practices such as mujahadah (inner striving), riyaḍah (spiritual discipline), and the cultivation of mahabbah (divine love), tawaḍu‘ (humility), and ikhlas (sincerity). These values permeate both ritual worship (‘ibadah mahḍah) and social conduct (‘ibadah ghayr mahḍah), fostering a mutasawwif persona who embodies balance between spiritual consciousness, intellectual maturity, and social responsibility. Ultimately, the pesantren emerges not only as a center of religious learning but as a dynamic agent of Islamic moderation (wasatiyyah), offering a contextual, peaceful interpretation of the Qur'an and the spiritual tradition of Islam as an effective antidote to violent extremism.